Interchangeability of Semiadjustable Articulators After 2 to 7 Years of Use - Han-Kuang Tan, BDS, MSD,1 Andrew Woo, DDS,2 Silvia Kim, DDS,2 (Blackwell Synergy, 2000)
The purpose of this study was to compare color, texture, and Shore A hardness of a resilient silicone denture liner with as-polymerized, roughened, or pumiced surfaces after treatment with perborate-, persulfate-, or hypochlorite-containing denture cleansers at 25°C or 55°C.